Labor income taxation, human capital and growth: the role of child care - Alessandra Casarico; Alessandro Sommacal (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper studies the implications of introducing child care in the human capital production function when assessing the effects of labor income taxation on growth. We develop an OLG model where formal schooling and child care enter the human capital production function as complements and we compare it with a model where only formal schooling matters for skill formation. Using a numerical analysis we find that, depending on the quality of child care services relative to parental care, the omission of child care from the technology of skills' formation can significantly bias the results related to the effects of labor income taxation on growth.
Keywords: J22; H31; 330; Taxation; growth; human capital production function; child care; labor supply; Bildungsinvestition; Kinderbetreuung; Arbeitsangebot; Lohnsteuer; Wirtschaftswachstum; Overlapping Generations; Theorie